PENGARUH PROFESIONALISME, KOMITMEN ORGANISASI DAN SENSITIVITAS ETIKA TERHADAP INTENSI DALAM MELAKUKAN WHISTLEBLOWING: STUDI KASUS PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) PROVINSI BALI - Ni Ketut Ayu Rosiana Dewi; I Gusti Ayu Agung Pradnya Dewi (Jurnal Ilmiah Akuntansi & Bisnis, 2019)
The Influence of Professionalism, Organizational Commitment and Ethical Sensitivity on Intention to Do Whistleblowing: Case of Asset and Finance Management Body of Bali Province.The purpose of this research is 1) To know the positive influence of Professionalism on Intensity in doing Whistleblowing case study in Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Bali. 2) To know the positive influence of Organizational Commitment on Intensity in doing Whistleblowing case study in Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Bali 3) To know the positive influence of Ethical Sensitivity on Intensity in doing Whistleblowing case study in Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Bali. Data collection techniques using questionnaires. The sample in this research were 167 employee of Badan Pengelola Keuangan dan Aset Daerah (BPKAD) Provinsi Bali. This study uses simple random sampling technique. Data were analysed using regression analysis techniques, descriptive statistic, determination, f-test, and t-test by software SPSS for windows. The results of the study found that 1) Professionalism has positive and significant effect on Intensity in doing Whistleblowing. 2) Organizational Commitment has positive and significant effect on Intensity in doing Whistleblowing. 3) Ethical Sensitivity has positive and significant effect on Intensity in doing Whistleblowing. Keywords: Professionalism, organizational commitment, ethical sensitivity, intensity in doing whistleblowing